2014
DOI: 10.1093/bmb/ldu021
|View full text |Cite
|
Sign up to set email alerts
|

The economics of medicines optimization: policy developments, remaining challenges and research priorities

Abstract: BackgroundThis review scopes the evidence on the effectiveness and cost-effectiveness of interventions to improve suboptimal use of medicines in order to determine the evidence gaps and help inform research priorities.Sources of dataSystematic searches of the National Health Service (NHS) Economic Evaluation Database, the Cochrane Database of Systematic Reviews and the Database of Abstracts of Reviews of Effects.Areas of agreementThe majority of the studies evaluated interventions to improve adherence, inappro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Many of the aims of medicines optimisation mirror those of medication reviews. Faria et al 38 reviewed the evidence on the effectiveness of medicines optimisation. They concluded that more research on outcomes and which pharmacist duties are most beneficial to patients is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the aims of medicines optimisation mirror those of medication reviews. Faria et al 38 reviewed the evidence on the effectiveness of medicines optimisation. They concluded that more research on outcomes and which pharmacist duties are most beneficial to patients is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In these terms, our findings support calls for more attention to be paid to economic evaluation of medication review. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…These results therefore suggest that having high levels of evidence‐based resources to reduce medication errors enables advanced‐level critical care pharmacists to focus on medicines optimisations, with the potential for important patient and health economic outcomes . Moreover, the resources identified provide a methodological basis for further research in this area designed to specifically investigate the related healthcare economics required to support wider application …”
Section: Discussionmentioning
confidence: 99%